Hope, goals, and pathways: Further validating the hope scale with observer ratings. Issue 4 (4th July 2019) - Cheavens, Jennifer S.; Heiy, Jane E.; Feldman, David B.; Benitez, Cinthia; Rand, Kevin L.
ABSTRACT: Objective : For the past two decades, hope theory has been an important framework for conceptualizing goal pursuits. Surprisingly there has been little effort to test the underlying suppositions of hope theory or to further validate the Hope Scale. Method : In Study 1, participants (N = 162, Mage  = 19, 61% female) completed the Hope Scale and nominated goals they would like to accomplish in the next few months. Goals were coded on several dimensions. In Study 2, participants (N = 118, Mage  = 19, 59% female) completed the Hope Scale, measures of optimism and self-efficacy, and generated workable pathways for achieving standardized goals. Results : Hope scores predicted setting objectively important, prosocial, long-term, and challenging goals. Hope (but not optimism or self-efficacy) was associated with generating more pathways for standardized goals. Conclusions : The results of these studies generally support the tenets of hope theory and provide further validation for the Hope Scale. As expected, people with higher hope were more likely than their lower-hope counterparts to engage in what has been considered successful goal-setting behavior. Hope is associated with important goal-relevant behaviors and efforts to increase hopeful thought may be important in helping individuals to move toward important life outcomes.